HESITANCY IN SECOND BOOSTER COVID-19 VACCINATION AND ITS ASSOCIATED FACTORS AMONG HEALTHCARE WORKERS IN BERA PAHANG: A CROSS-SECTIONAL STUDY - Alias, Azulaikha; Avoi, Richard; Azhar, Nurliyana; Wan Mohamad Lotfi, Wan Hafizu Nazrin; Mohd Zali, S Muhammad Izuddin Rabbani; Nurkamila Mohamed Hassan; Safaridah Anuar; Mohamad Lokman Hakim Mat Isar (Malaysian Journal of Public Health Medicine, 2025)
Healthcare workers (HCWs) in Malaysia play a key role in controlling COVID-19 through prevention, treatment, and vaccination. Since the national vaccine rollout in March 2021, booster doses have been recommended. However, hesitancy toward the second booster dose among HCWs is a growing concern that could affect public health outcomes. This cross-sectional study aims to determine the prevalence and factors associated with hesitancy in the second booster COVID-19 vaccine among healthcare workers in Bera, Pahang. Data were collected from April to May 2023 using a self-administered, validated questionnaire across all health facilities in the district. Simple logistic regression was used to determine the association between the independent and dependent variables, while multiple logistic regression identified significant predictors of hesitancy. A total of 400 healthcare workers participated, with 45.2% (181) exhibiting high hesitancy toward the second booster (95% CI: 40.32, 50.07). Four significant factors were identified which included older age being associated with higher hesitancy (OR = 1.73; 95% CI = 1.03, 2.91; p = 0.037), moderate to severe side-effects of previous COVID-19 vaccination (OR = 2.499; 95% CI = 1.483, 4.209; p-value <0.001), negatives attitudes (OR = 3.293; 95 % CI = 1.699, 6.383; p-value <0.001) and high conspiracy belief (OR = 3.520; 95% CI = 2.175, 5.697; p-value <0.001 ). This study shows the urgent need for targeted efforts to improve vaccine confidence among HCWs. Tackling misinformation and building trust are key strategies. This study highlights the need for clear, targeted messages to support healthcare workers and public health.